Hypolipidemic Effects of Pea Protein Hydrolysates on Lipid Profile and Uric Acid in Cisplatin-Induced Nephropathy Rats - Hidayat, Meilinah; Prahastuti, Sijani; Soemardji, Andreas A; Hasan, Khomaini; Audrey, Gabriella; Gabriella, Janifer; Luvina, Petrisia; Liempapas, Cicilia; al, et (Journal of Medicine and Health, 2019)
The usage of Cisplatin (CP) can cause side effects such as toxicity and impaired kidneyfunction. Poor kidney function causes dyslipidemia and hyperuricemia. Researchers in Canadastate that pea protein hydrolysates can improve kidney function. The aim was to examine thehypolipidemic effect of 8 types of pea protein hydrolysate on lipid profiles and uric acid in CPinduced rats in purpose to find protein sources origin of Indonesia for kidney therapy. This is atrue experimental study using fifty female Wistar rats divided into 10 treatment groups.Weadministered 8 types of pea protein hydrolysate for 30 days. On day 7 all rats (except negativecontrol) were induced CP intraperitoneally. Study parameters was evaluated on days 12 and30. In general, all treatments showed good hypolipidemic effects, and differed significantly fromCP group (p <0.01). The group that showed lowest total cholesterol, LDL and triglycerideresults is yellow pea protein hydrolysate Neutrase; HDL: green peas protein hydrolysatebromelain, uric acid: protein hydrolysate of pea protein isolate bromelain. As conclusion,protein hydrolysates of pea has good hypolipidemic effects on Lipid profile and Uric Acid inCP-induced nephropathy Rats. Keywords: protein hydrolysates, green peas, neutrase, bromelain, lipid profiles